THE INFLUENCE OF LEADERSHIP STYLE AND TEAMWORK ON SATISFACTION WORK EMPLOYEE WITH ENVIRONMENT WORK AS MODERATING VARIABLES AT PUBLIC HEALTH CENTER X BATAM CITY - Noviyanti Noviyanti; Muammar Khaddafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Destination Study this is for now and analyze influence style leadership and cooperation team to satisfaction work employee with environment work as moderating variable. Method research used is quantitative correlation. Population is the employee who work at public health center X Batam City with total 40 people, with technique sample is the total sampling. Data in the form of primary data with a questionnaire instrument and a scale likert. Quantitative data analysis techniques with method Partial Least Square (PLS) statistics. Research results got that style leadership take effect positive and significant to variable satisfaction work, Teamwork is influential positive and not significant to variable performance. Environment work take effect positive and not significant to variable satisfaction work. Leadership style with environment work take effect close to satisfaction work, while teamwork _ with environment work take effect weak to satisfaction work. Conclusion that only there is one variable that has influence significant with Pvalue 0.004 < = 0.05 and has connection close with variable the moderator that is variable leadership to satisfaction affected work by closely by variable environment work.